Supporting Self-Employment and Small-Scale Entrepreneurship : Potential Programs to Improve Livelihoods for Vulnerable Workers - Cho, Yoonyoung; Robalino, David; Watson, Samantha (World Bank Group, Washington, DC, 2014)
Worldwide, around 55 percent of workers are self-employed, and about three-quarters of these are likely to be subsistence entrepreneurs. These self-employed workers include farmers and own-account workers, many of whom work in small household enterprises without pay. A large proportion of these workers live in poor or vulnerable households. In Sub-Saharan Africa, for instance, close to 80 percent of the self-employed are poor. While numerous countries have adopted programs that aim to promote self-employment and small-scale entrepreneurship (SSE), the design of such programs seems ill suited to respond to the needs of those who engage in entrepreneurial activities not by choice, but by necessity. This note discusses the potential public policy role of programs aimed at improving the livelihoods of subsistence entrepreneurs . It begins by looking at the characteristics of self-employed workers, the different types of entrepreneurs, and the constraints they face. It then analyzes the potential role of public policy in improving the earning opportunities of subsistence entrepreneurs, the types of programs that could be used, and general issues to be considered when designing and implementing pilot interventions. The note has four main messages: identify interventions to support subsistence entrepreneurs, the evidence of what works is limited, interventions that complement safety net programs, adopt a more systematic approach to designing, implementing, and evaluating new programs.